Implementation Plan, Organize, Act, and Control In the Management of Sports Facilities Pesantenan Pati Regency - Agung Supriyanto; Limpad Nurrachmad (Universitas Sriwijaya, 2023)
This study aims to describe the management functions of Plan, Organize, Act, and Control (POAC), constraints, and user responses to the management of sports halls (GOR) Pesantenan Pati Regency. Approach Qualitative research was used with the aim of managing GOR Pesantenan facilities and their respondents are managers, coaches, and athletes. The data source sample was selected by purposive and snowball sampling, with data collection through observation, interviews, and documentation, then analyzed using theory Miles and Huberman. The results showed that the function of planning (Planning) on the management GOR Pesantenan Pati Regency is not mature and not good enough, while the function of organizing (organizing) has been done well. The actuating function is not good, while the function control has been running well. Constraints in some damage to the facility requires repair and maintenance, while the challenges faced are GOR speci?cations still versatile. User response shows the number of complaints about damage to the facility sport that needs improvement. In conclusion, the management of GOR Pesantenan in Pati Regency is necessary improve planning and actuation functions, as well as improve maintenance on sports facilities can meet the needs of users and provide better service. This research can be reference for the development of sports facility management in other areas.